Study of Hartmanns Pouch of the Gallbladder (Delta Medical College Journal, 2014)
Background: The gall bladder is a hollow pear shaped sac lying within a fossa on the visceral surface of the right lobe of the liver. In the junction of neck of the gallbladder and the cystic duct, there is a pouch present called Hartmans pouch or infundibulum of the gallbladder which is a frequent but inconstant feature of the normal gallbladder. It is the common site of lodged gallstones. Objective: To determine the proportion of presence of Hartmans pouch in our population so that the concerned personnel might have a thought in mind that common pathologies of gall bladder may also involve this pouch. Materials and method: This cross sectional study was carried out in the department of Anatomy, Sir Salimullah Medical College & Mitford Hospital, Dhaka, Bangladesh, from July 2010 to June 2011. The number of sample was 62 postmortem human gallbladders which were collected from unclaimed dead bodies. Results: Hartmanns pouch of the gallbladder was found in 45 (72.58%). Conclusion: Hartmans pouch is present in a good proportion of our population. DOI: http://dx.doi.org/10.3329/dmcj.v2i2.20527 Delta Med Col J. Jul 2014; 2(2): 68-70